1946
DOI: 10.1021/ie50440a032
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value of Canned Foods.

Abstract: ITRUS juices have long C been regarded as excellent sources of vitamin C (ascorbic acid) and have been shown to contribute significant amounts of the vitamin to the average American diet.From the standpoint of convenience and economy the canning of citrus juices has made available to the general public a n excellent source of this vitamin. The retention of ascorbic acid during canning operations and subsequent storage becomes of paramount importance in evaluating the nutritional value of canned citrus iuices.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1948
1948
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…At this temperature SSGJ retains more AA than is retained in SSOJ under similar conditions. Higher percent retentions of AA in SSGJ than in SSOJ at high storage temperatures and different storage periods have been reported (Lamb, 1946). As expected, the rate of AA degradation in SSGJ increased with temperature.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…At this temperature SSGJ retains more AA than is retained in SSOJ under similar conditions. Higher percent retentions of AA in SSGJ than in SSOJ at high storage temperatures and different storage periods have been reported (Lamb, 1946). As expected, the rate of AA degradation in SSGJ increased with temperature.…”
Section: Resultssupporting
confidence: 58%
“…Loss of AA in single-strength grapefruit juice (SSGJ) has been shown to be related to storage time and temperature (Moore et al, 1944;Riester et al, 1945;Lamb, 1946;Moschette et al, 1947;Sheft et al, 1949;Moore, 1949;Freed et al, 1949;Heikal et al, 1967). In those studies, however, TAVC was not determined and most of those studies did not cover a wide range of storage temperatures.…”
mentioning
confidence: 99%
“…ascorbic acid retention was decidedly better. According to Lamb (1946), storage a t 2l0C.(70"F.) results in approximately a one per cent per month decrease in the ascorbic acid in citrus juices.…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…Prolonged Xtorage: Although some decline of ascorbic acid may be associated with long storage of canned foods, Guerrant et al (1945), Lamb (1946), Olliver (1936, and Riester et ul. 1945), the extent of the decline after the first few weeks appears to be associated with the type of the product and the storage temperature.…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…The susceptibility of vitamin C (ascorbic acid) to oxidation in aqueous solution and the dependence of the reaction on the presence of dissolved and headspace oxygen has been recognized (Bauernfeind, 1953). Lamb (1946) claimed an 8% drop in 6.5 months in the ascorbic acid content of canned orange juice. A study by Kefford et al (1959) revealed the oxidative destruction of ascorbic acid in canned pasteurized orange juice occurred only during the first few days until the free oxygen disappeared.…”
mentioning
confidence: 99%